2012
DOI: 10.3390/ijms131114788
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanol in Blood as a Marker of Chronic Alcohol Use: A Systematic Review and Meta-Analysis

Abstract: The present paper aims at a systematic review of the current knowledge on phosphatidylethanol (PEth) in blood as a direct marker of chronic alcohol use and abuse. In March 2012, the search through “MeSH” and “free-text” protocols in the databases Medline/PubMed, SCOPUS, Web of Science, and Ovid/Embase, combining the terms phosphatidylethanol and alcohol, provided 444 records, 58 of which fulfilled the inclusion criteria and were used to summarize the current evidence on the formation, distribution and degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
188
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(207 citation statements)
references
References 82 publications
(142 reference statements)
2
188
2
7
Order By: Relevance
“…One study showed good agreement, with a mean difference of 95.8 ng/mL (RSD=3.0%) and -4. In literature, HPLC-ELSD methods analysing total PEths in blood generally used cut-off values between 0.2 and 1 µmol/L [7,10,11,17,19] to detect alcohol consumption. In Sweden, 0.7 µmol/L of total PEths is used as the clinical threshold [7].…”
Section: Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…One study showed good agreement, with a mean difference of 95.8 ng/mL (RSD=3.0%) and -4. In literature, HPLC-ELSD methods analysing total PEths in blood generally used cut-off values between 0.2 and 1 µmol/L [7,10,11,17,19] to detect alcohol consumption. In Sweden, 0.7 µmol/L of total PEths is used as the clinical threshold [7].…”
Section: Methods Validationmentioning
confidence: 99%
“…The half-life of PEths in whole blood was calculated to be 4.0 ± 0.7 days [3]. In case of chronic/excessive alcohol consumption, PEths are detectable in blood up to 28 days after sobriety [10]. Moreover, quantification of PEths can be used to detect the degree of alcohol consumption as a significant correlation between the PEths concentrations in blood and the amount of consumed ethanol has been demonstrated [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to an elimination half-life of about four days [17], accumulation of PEth is observed after repeated drinking. Therefore, PEth has been discussed as marker for detection of prolonged excessive alcohol consumption in several studies [16,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However the 100 to 1000 fold higher affinity of PLD for alcohol promotes the transphosphatidylation of alcohol and PC, therefore PEth is always formed when alcohol is present [12,13]. Due to the half-life of 4 to 5 days, PEth however can be detected up to at least two weeks on average in blood [14]. This relatively long half-life compared to for instance EtG makes PEth a promising retrospective marker for alcohol consumption detectable in blood.…”
Section: Phosphatidylethanol (Peth)mentioning
confidence: 99%